Application of Lean UX and System Usability Scale (SUS) Methods in Redesigning User Interface and User Experience on Adella Hospital Online Registration Website - Sabrina Desy Rahmawati; Budi Prasetiyo (Journal of Advances in Information Systems and Technology, 2024)
This research aims to evaluate user experience of a hospital online registration website. The SUS method will be used to accurately measure users’ experience. Testing using SUS is carried out by distributing a questionnaire containing 10 SUS template questions and 13 general questions. After the questionnaire is distributed, the collected data will be processed using SUS assessment standards. In addition, several respondents will be interviewed in order to design a new website prototype. The prototype will be developed using Lean UX method. Testing design improvements using Lean UX method shows improvements compared to the old design.